Microeconomic Consequences and Macroeconomic Causes of Foreign Direct Investment in Southern African Economies - Lederman, Daniel; Mengistae, Taye; Xu, Lixin Colin (2012)
The causes and consequences of foreign direct investment (FDI) in developing countries remains a subject of debate among researchers and policymakers alike. The authors use international data and a new micro-data set of firms in thirteen Southern African Developing Countries (SADCs) to investigate the benefits and determinants of FDI in this region. FDI appears to have facilitated local development in the SADC region. Foreign firms tend to perform better than domestic firms, tend to be larger, are located in richer and better-governed countries and in countries with more competitive financial intermediaries, and they are more likely to export than domestic firms. They also exhibit positive spillover effects to domestic firms. Relying on a standard model to predict the country-level FDI inflows per capita, the authors find that SADC is attracting their expected level of FDI inflows, at least relative to its income level, human capital, demographic structure, institutions, and economic track record. There are some differences between SADC and the rest of the world in FDI behavior: in SADC, the income level is less important and openness more so. The authors use two comparison groups to compare with SADC to shed light on why other regions have attracted more FDI per capita than SADC. The factors that explain SADC s low FDI inflows are economic fundamentals (e.g., previous growth rates, average income, phone density, and the adult share of population).